Thermal performance in heat exchangers by the irreversibility, effectiveness, and efficiency concepts using nanofluids - Nogueira E. (Журнал інженерних наук)
The objective of the work is to obtain the outlet temperatures of the fluids in a shell and tube heat exchanger. The second law of thermodynamics is applied through the concepts of efficiency, effectiveness, and irreversibility to analyze the results. Water flows in the shell, and a mixture of water-ethylene glycol is associated with fractions of nanoparticles flows in the tube. Water enters the shell at 27 °C, and the mixture comes to the tube at 90 °C. The mass flow is kept fixed in the shell, equal to 0.23 kg/s, and varies between 0.01 kg/s to 0.50 kg/s. Volume fractions equal to 0.01, 0.10, and 0.25 were considered for analysis, for both nanoparticles from Ag and Al2O3. Results for Reynolds number, heat transfer rate, efficiency, effectiveness, and irreversibility are presented for critique, discussion, and justification of the output data found. It is shown that the flow regime has a significant effect on the performance of the analyzed heat exchanger.